2006
DOI: 10.1152/ajpregu.00247.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vagal afferents are essential for maximal resection-induced intestinal adaptive growth in orally fed rats

Abstract: Small bowel resection stimulates intestinal adaptive growth by a neuroendocrine process thought to involve both sympathetic and parasympathetic innervation and enterotrophic hormones such as glucagon-like peptide-2 (GLP-2). We investigated whether capsaicin-sensitive vagal afferent neurons are essential for maximal resection-induced intestinal growth. Rats received systemic or perivagal capsaicin or ganglionectomy before 70% midjejunoileal resection or transection and were fed orally or by total parenteral nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…33 Indeed our study confirmed increased expression of proglucagon mRNA in ileum following resection. One aim of this study was to assess whether exogenous GLP-2 down-regulates endogenous proglucagon expression.…”
Section: Discussionsupporting
confidence: 77%
“…33 Indeed our study confirmed increased expression of proglucagon mRNA in ileum following resection. One aim of this study was to assess whether exogenous GLP-2 down-regulates endogenous proglucagon expression.…”
Section: Discussionsupporting
confidence: 77%
“…Control animals did not undergo a transection, so that the effects of GLP-2 on intact bowel could be compared with the effects on resected bowel. This methodology dose not allow for an assessment of the effects of transection alone; transection has been shown to alter motility, neuronal, and potentially adaptation in previous studies, and so is important physiologically, but would not be done in isolation clinically [17]. Animals were followed until d 3 or 10 postsurgery, and further divided into groups receiving GLP-2 (10 g/kg given i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Following intestinal resection, the remaining intestine efforts to compensate the loss off functional intestinal surface by adaptive changes (2,(14)(15)(16)(17). In animal models, enteral nutrition stimulates brush-border enzyme activities, including maltase and sucrase, villus height, crypt depth, cell proliferation, and reduces apoptosis (15,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Following intestinal resection, the remaining intestine efforts to compensate the loss off functional intestinal surface by adaptive changes (2,(14)(15)(16)(17). In animal models, enteral nutrition stimulates brush-border enzyme activities, including maltase and sucrase, villus height, crypt depth, cell proliferation, and reduces apoptosis (15,(17)(18)(19)(20). PN is a lifesaving treatment when enteral absorption is insufficient to provide nutritional requirements (21), but in combination with enteral nutrient deprivation it predisposes to mucosal atrophy, loss of intestinal barrier function, and IF-associated liver disease (3,5,(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation